Evaluation of Retinol Level Among Preschool Children, Pregnant and Lactating Women Attending Primary Health Care Centres in Baghdad - Hadi, Sawsan Mohammed Ali; Hussien, Alaa Shaalan; Ali, Saad Alddin Hussien; Jabber, Azhar Abdul; Rejeb, Ahmed; Hammed, Ali (International Journal of Child Health and Nutrition, 2013)
Background: Vitamin A deficiency (VAD) is a major public health nutrition problem in the developing world. There have been no studies on this topic in Iraq. This study was designed to evaluate the serum retinol levels of preschool children, pregnant and lactating women. Objectives: The present study is an attempt to estimate the prevalence of vitamin A deficiency among preschool children, pregnant and lactating women attending primary health care centers in Baghdad, in addition to figure out the relation between vitamin A deficiency with some demographical, clinical, variables. Subjects and Methods: The study was conducted during the period from October to December 2009. The sample was comprised of 490 subjects, Lactating women pregnant women and under 6 year’s old children attending ten primary health care centers in Baghdad. The data were collected through direct interview; blood samples were taken and analyze for serum retinol (SR) by HPLC analysis and hemoglobin (Hb) level, anthropometric measurement were obtained for the study sample. Results: The study showed that the prevalence of vitamin A deficiency in preschool aged children (below 6 years) was (38.3 %); and that for lactating women and pregnant women were (7.1 %) and (25 %) respectively. Forty percent of pregnant women, (25.8 %) of lactating women and a total of (58.6 %) preschool children were anemic, A correlation coefficient between SR and Hb concentrations was significant (N=490, r=0.533, P<0.0001). Conclusion: Vitamin A deficiency is a public health problem, this study shows that subjects in the 3 groups (preschool children, pregnant and lactating women) are at risk of VAD and anemia; nearly half of them had the co-occurrence of VAD and anemia. A close association between vitamin A deficiency and anemia with a correlation coefficient between SR and Hb concentrations was significant.